2021
DOI: 10.3389/fnrgo.2021.679033
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation to Assess Exercise-Induced Neuroplasticity

Abstract: Aerobic exercise facilitates neuroplasticity and has been linked to improvements in cognitive and motor function. Transcranial magnetic stimulation (TMS) is a non-invasive technique that can be used to quantify changes in neurophysiology induced by exercise. The present review summarizes the single- and paired-pulse TMS paradigms that can be used to probe exercise-induced neuroplasticity, the optimal stimulation parameters and the current understanding of the neurophysiology underlying each paradigm. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 144 publications
0
8
0
1
Order By: Relevance
“…A change in corticospinal excitability following an acute bout of exercise is suggested to indicate that neuroplasticity has been induced. As reviewed previously ( Turco and Nelson, 2021 ), studies have reported inconsistent changes in TMS measures following aerobic exercise. As an example, a single session of aerobic exercise has been reported to increase ( Lulic et al, 2017 ; Neva et al, 2017 ; El-Sayes et al, 2019b ; MacDonald et al, 2019 ; Nicolini et al, 2020 ) or not change ( McDonnell et al, 2013 ; Singh et al, 2016 ; Brown et al, 2020 ; El-Sayes et al, 2020 ) corticospinal excitability as assessed with motor-evoked potentials (MEPs).…”
Section: Exercisementioning
confidence: 88%
See 1 more Smart Citation
“…A change in corticospinal excitability following an acute bout of exercise is suggested to indicate that neuroplasticity has been induced. As reviewed previously ( Turco and Nelson, 2021 ), studies have reported inconsistent changes in TMS measures following aerobic exercise. As an example, a single session of aerobic exercise has been reported to increase ( Lulic et al, 2017 ; Neva et al, 2017 ; El-Sayes et al, 2019b ; MacDonald et al, 2019 ; Nicolini et al, 2020 ) or not change ( McDonnell et al, 2013 ; Singh et al, 2016 ; Brown et al, 2020 ; El-Sayes et al, 2020 ) corticospinal excitability as assessed with motor-evoked potentials (MEPs).…”
Section: Exercisementioning
confidence: 88%
“…Further, short-interval intracortical inhibition (SICI), an assessment of primary motor cortex (M1) microcircuitry, has been reported to decrease ( Singh et al, 2014 ; Smith et al, 2014 ; Stavrinos and Coxon, 2017 ; Yamazaki et al, 2019 ) or not change ( Mooney et al, 2016 ; Andrews et al, 2020 ; Morris et al, 2020 ; Hu et al, 2021 ) following a single session of aerobic exercise. Studies have also shown inconsistent effects of aerobic exercise on other common TMS measures including the contralateral silent period (CSP), intracortical facilitation (ICF), long-interval intracortical inhibition (LICI), and short-latency afferent inhibition (SAI) (see Turco and Nelson, 2021 ). Table 1 provides descriptions of the neurophysiological and molecular measures of neuroplasticity that are discussed in this review.…”
Section: Exercisementioning
confidence: 99%
“…Future studies should consider normalizing recorded SEP amplitudes to parameters of the peripheral nerve volley, e.g., N9 potentials recorded over the brachial plexus (Nuwer et al, 1994) to refine conclusions about possible neuroplasticity. Similar approaches can be found in studies normalizing TMS parameters to M-waves (Turco and Nelson, 2021) or H-reflexes to M-waves (Grosprêtre and Martin, 2012). Furthermore, modeling studies should be undertaken to quantify and potentially eliminate the influence of tissue architecture on SEP amplitudes.…”
Section: Limitations and Recommendations For Future Studiesmentioning
confidence: 92%
“…To date, it remains incompletely understood which physiological and specifically which neurophysiological markers underlie peak athletic performance. Accordingly, novel approaches have been proposed for neurodiagnostic in sports, using neurostimulation methods such as transcranial magnetic stimulation (TMS) (Turco and Nelson, 2021 ) as well as imaging methods such as magnetic resonance imaging (MRI), electroencephalography (EEG), and functional near-infrared spectroscopy (fNIRS) to identify markers of training-induced neuroplasticity in athletes (Seidel-Marzi and Ragert, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches for conditioning repetitive TMS (rTMS) have recently emphasized. One of which is short-duration rTMS with low-intensity and high-frequency stimulation and is called ‘theta-burst’ stimulation, whereas the other is the direct application of weakly negative or constant positive currents on the scalp to enact changes in brain impulses [ 102 ]. In a recent study, it was also found that four continuous rTMS sessions can recover refractory central neuropathic pain over three weeks by applying electromagnetic induction of 20 Hz on the primary motor cortex [ 103 ].…”
Section: Interventional Methods As An Effective Treatment Approach Ag...mentioning
confidence: 99%